Analysis of the Effect of Vuca on Mental Health After the Covid-19 Pandemic - Roida Pakpahan (Journal of Information System, Informatics and Computing, 2022)
In the VUCA era, mental health is a very important aspect that must be owned so that every individual remains productive and happy in the midst of uncertainty. The Covid-19 pandemic has made the VUCA condition even more real, making people directly feel the volatility, uncertainty, complexity and ambiguity (VUCA). World health organization (WHO) states mental health problems have increased height during the Covid-19 pandemic. This is because during the Covid-19 pandemic, many people have lost their jobs, sources of income and deep sorrow over the loss of loved ones. On the other side, Covid-19 carried out volality, changes in the order of life from conventional systems to digital systems. Digital transformation makes the intensity of VUCA increase. This study aims to analyze of the effect of VUCA on mental health after the Covid-19 pandemic. The research results show that VUCA affects people's mental health. Covid-19 is part of VUCA, uncertainty which causes uncertainty in the world economy and leaves deep scarring effects, making problem even more complex. Uncertainty is the main factor that triggers mental health problems. The tendency to perceive uncertainty negatively makes people vulnerable to experiencing mental health problems, depression and anxiety. VUCA creates a new paradigm, it requires spiritual intelligence and mental resilience, self-awareness and the ability to respond well to change in order to survive in the midst of uncertainty. Growth mindset and learning agility so that they are capable of facing various challenges in the VUCA Era, because true life is a learning.